Business Ethics Violations in Accounting Practices: a Case Study of Financial Statement Manipulation at PT Garuda Indonesia - Adinda Priski Dhea Asiyanti; Sri Trisnaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study examines the breach of business ethics in accounting practices in the case of PT Garuda Indonesia, where the company manipulated its financial statements for the 2018 fiscal year. The manipulation involved recognizing unrealized revenue, which contravened generally accepted accounting principles and financial reporting standards applied by the Financial Accounting Standards (SAK) in Indonesia. This research explores the impact of these manipulative actions on the company’s integrity, stakeholder trust, and market reputation. Additionally, the study discusses the business ethics principles violated in this case, such as integrity, transparency, and professional responsibility, while proposing recommendations to improve accounting practices and ethical oversight in corporate financial reporting. The findings of this research are expected to provide insights for other companies in implementing high ethical standards and preventing similar violations in the future.